Competition during enrichment of pathogenic Escherichia coli may result in culture bias - Cheyenne C. Conrad; Kim Stanford; Tim A. McAllister; James Thomas; Tim Reuter (Canadian Science Publishing, 2016)
Deadly outbreaks and illnesses due to Shiga toxin-producing Escherichia coli (STEC) occur worldwide; however, the cultivation methods required for adequate monitoring and traceback investigations are inefficient at best. Detection of STEC relies heavily on enrichment; yet no standard media or protocols exist. Furthermore, whether enrichment may bias detection of multiple STEC serogroups from complex samples is unknown. Thus, 14 STEC strains of serogroups O157 and the top six non-O157s (O26, O45, O103, O111, O121, and O145) were enriched in pairs for 6-78 h in broth and evaluated by quantitative polymerase chain reaction (qPCR). Here we show that a conventional 6-h enrichment protocol did not result in intra-species culture bias for the isolates tested. However, subsequent enrichments often produced biased cultures, with differences in the qPCR gene copy number ≥2 log10 apparent in 12%, 38%, and 52% of competitions after 30, 54, and 78 h of consecutive enrichments, respectively. Some strains were able to prevail and (or) out-compete the opponent strain in 100% of competitions. Our results suggest that culture bias should be considered and (or) evaluated further due to the potential implications during routine pathogen screening and outbreak investigations.